2001
DOI: 10.1002/1521-3765(20010216)7:4<791::aid-chem791>3.0.co;2-2
|View full text |Cite
|
Sign up to set email alerts
|

The Importance of Mesomerism in the Termination ofα-Carboxymethyl Radicals from Aqueous Malonic and Acetic Acids

Abstract: In the dioxygen-free aqueous malonic and acetic acid systems. alpha-carboxymethyl radicals are produced through hydrogen abstraction from the parent compound by radiolytically generated OH radicals. H abstraction from the CO2-/CO2H group followed by decarboxylation is a process of small importance (< or = 5%). The alpha-carboxymethyl radicals terminate by recombination. Two types of recombination product are observed which are characterised by the formation of a C-C linkage or a C-O linkage. alpha-Carboxymethy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 20 publications
2
9
0
Order By: Relevance
“…The Å CH 2 COO À radical is comparatively stable (Wang et al, 2001). The organic P compounds are broadly grouped into three sets: the P-acetyl compounds, the P-CH 2 compounds, and phosphonoformate (Fig.…”
Section: Proposed Organic Phosphorus Reaction Pathwaysupporting
confidence: 73%
“…The Å CH 2 COO À radical is comparatively stable (Wang et al, 2001). The organic P compounds are broadly grouped into three sets: the P-acetyl compounds, the P-CH 2 compounds, and phosphonoformate (Fig.…”
Section: Proposed Organic Phosphorus Reaction Pathwaysupporting
confidence: 73%
“…Abstraction of a hydrogen atom from glycolate 5 by a sulfite radical generates the hydroxy-carboxymethyl radical 24 whilst redox compensatory reduction of 5 generates the carboxymethyl radical 25 . Dimerization of 24 produces the tartrates 9 whereas dimerization of 25 produces succinate 32 as well as acetate 6 and glycolate 5 37 . Recombination of radicals 24 and 25 provides one route to malate 31 , a second would be from reduction of 9 .…”
Section: Resultsmentioning
confidence: 99%
“…Dimerization of 24 produces the tartrates 9 whereas dimerization of 25 produces succinate 32 as well as acetate 6 and glycolate 5 32 . Recombination of radicals 24 and 25 provides one route to malate 31, a second would be from reduction of 9.…”
Section: S19 -S23)mentioning
confidence: 99%
“…Studies have shown that acetic acid, one of the products for the reaction between Hg II and malonic acid (Table 2), could be produced from the recombination of acetic acid radical followed by hydrolysis at acidic conditions (29).…”
Section: Reaction Mechanismmentioning
confidence: 99%